Verification of an articulated arm coordinate measuring machine using a laser tracker as reference equipment and an indexed metrology platform. (June 2015) - Acero, R.; Brau, A.; Santolaria, J.; Pueo, M.
Highlights: Validation of LT use as reference instrument for AACMM verification procedures. Testing time and positions complexity reduction with indexed metrology platform. Avoids generation of physical reference lengths and use of conventional gauges. Increased flexibility for defining test positions and reference lengths. Abstract: In this work the analysis of the use of a laser tracker as a reference instrument in calibration and verification procedures for articulated arm coordinate measuring machines (AACMM) with an indexed metrology platform is presented. In the case of AACMM verification procedures, where it is necessary to evaluate its maximum working volume, this technique represents an alternative to conventional one-dimensional gauges and avoids the need of materializing the lengths required for a conventional gauge by increasing the flexibility for defining test positions and broadening the definition of reference test lengths depending on equipment calibration or verification requirements. First a procedure for the AACMM verification with the indexed metrology platform (IMP) and the laser tracker (LT) used as a reference instrument was defined and the required accuracy of the equipment was assessed. The experimental testing to validate its proper application was carried out by means of laser tracker measurements of six retroreflector targets located in a mesh that simulated the AACMM working volume. Finally, the results obtained with both equipment, laser tracker and AACMM with indexed metrology platform, showed that the procedure presented is suitable and that the laser tracker could be considered as a reference instrument for AACMM verification processes when the nominal accuracy of the laser tracker is assured.